Defunct federalisms critical perspectives on federal failure - Kavalski, Emilian; Zolkos, Magdalena (Federalism studies, 2008)
Ideal for advanced undergraduates and graduate students as well as university lecturers and researchers working on the issues related to contemporary federalism, history of federal units and the questions of national identity.